2008
DOI: 10.1142/s0192415x0800562x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Activities of Cirsium setidens NAKAI against CCl4-Induced Liver Damage

Abstract: The antioxidant activity and hepatoprotective potential of Cirsium setidens Nakai, a widely used medicinal plant, were investigated. The n-butanol (n-BuOH) fraction of leaves and roots of C. setidens had a higher 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity than the other soluble fractions. The n-BuOH fraction of roots of C. setidens had a significant hepatoprotective activity at a dose of 500 mg/kg compared to that of a standard agent. The biochemical results were confirmed by histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Liver detoxification occurs in two phases, namely phase I (involving oxidation, reduction, and hydrolysis) and phase II (involving synthetic conjugations with sulfates, glucuronic acid, glutathione, acetate, and glycine), and these phases convert toxic materials into harmless metabolites and then excrete them from the body [7]. Liver diseases are considered serious problems which can be caused by toxic chemicals, drugs, and virus infiltration through ingestion or infection [8]. These toxins induce the production of reactive oxygen species (ROS), which can attack hepatic tissue and cause serious injury [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Liver detoxification occurs in two phases, namely phase I (involving oxidation, reduction, and hydrolysis) and phase II (involving synthetic conjugations with sulfates, glucuronic acid, glutathione, acetate, and glycine), and these phases convert toxic materials into harmless metabolites and then excrete them from the body [7]. Liver diseases are considered serious problems which can be caused by toxic chemicals, drugs, and virus infiltration through ingestion or infection [8]. These toxins induce the production of reactive oxygen species (ROS), which can attack hepatic tissue and cause serious injury [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Liver tissue injury can be caused by the ingestion of chemicals or drugs or by infection through virus infiltration [6]. Among them, carbon tetrachloride (CCl 4 ) is commonly used to study hepatotoxicity in animal models [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The young leaves and stems of C. setidens are edible and rich in nutrients including calcium and vitamin A 5 . It has been reported that Cirsium species including C. setidens contains bioactive phytochemicals with various medicinal activities such as anti-oxidant, anti-cancer, anti-tumor, and anti-inflammatory activities 3,[6][7][8][9][10][11][12][13] . Pectolinarian (C 29 H 34 O 15 ) belong to a group of flavones is reported to be common in the genus Cirsium, and the aglycone of pectolinarian prevents galactosamine-induced hepatic inflammatory activity by inhibiting eicosanoid formation in inflammatory lesions 7,12 .…”
Section: Introductionmentioning
confidence: 99%